Research on the influence of distributed generation and its grid connection on power system. Issue 1 (1st April 2022) - Wu, Zhongchao
Abstract: China's per capita resources are scarce and consumed very quickly. New energy power generation has the characteristics of green, environmental protection and renewable, and it is the main development direction of the current and future power industry. With the continuous expansion of new energy power generation and grid-connected scale, various adverse effects brought to the power grid in the process of grid-connected are gradually emerging and becoming more and more serious.This paper briefly introduces the distributed power generation, and then studies and analyzes various problems brought by the grid connection of new energy to the power system from the four aspects of grid voltage, grid harmonics, grid frequency, and grid protection, and gives some solutions. For example, if the power generation equipment meets the grid-connection standard, a real-time monitoring device for power quality and a dynamic reactive power compensation device can be installed; for harmonic pollution problems, multi-pulse converters and power filter devices can be used; for power quality problems in the distribution network, the structure of the power grid can be optimized., Reasonable selection of the impedance ratio of the circuit, etc.